Determination of Trace Elements in Some Moss Samples by Atomic Absorption Spectrometry - OZDEMIR, TURAN; MENDIL, DURALI (Asian Journal of Chemistry, 2010)
In the present work, the trace metal levels in moss samples were determined. Six species of moss samples were collected from near the Artvin motorway in Turkey. Fe, Cu, Mn, Zn, Pb and Cd in the samples were analyzed using flame and graphite furnace atomic absorption spectrometry after microwave digestion. The metal concentrations in samples were found to be 1076.0-2137.0, 13.3-28.6, 107.7-375.6, 86.8-134.1, 8.3- 27.6 and 0.2-1.3 μg/g for iron, copper, manganese, zinc, lead and cadmium, respectively.